2004
DOI: 10.1080/00365520410005911
|View full text |Cite
|
Sign up to set email alerts
|

Gastric acid secretion of normal Japanese subjects in relation to Helicobacter pylori infection, aging, and gender

Abstract: In Japanese subjects, aging affects gastric acid secretion differently depending on the status of H. pylori infection. H. pylori infection showed a stronger inhibitory effect on the acid secretion in men than in women. This gender-related difference in the susceptibility of acid secretion to H. pylori infection may explain the higher rates of gastric cancer in men in Japan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
39
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(47 citation statements)
references
References 43 publications
6
39
0
Order By: Relevance
“…[18][19][20][21][22][23][24][25] The prevalence of H. pylori infection is generally supposed to increase with age. 26 More recently, it was reported in Japan, that the prevalence of positive rate of serum anti-H. pylori-IgG as well as H. pylori infection detected histological and by the 13 C-urea breath test is decreasing in longliving elderly, leading to a concomitant decrease of Helicobacter pylori virulence factors A Soltermann et al the prevalence of gastric cancer in subjects older than 85 years. 27 Concerning IM, the authors reported an increase with age in either H. pylori-negative or -positive patients.…”
Section: Discussionmentioning
confidence: 99%
“…[18][19][20][21][22][23][24][25] The prevalence of H. pylori infection is generally supposed to increase with age. 26 More recently, it was reported in Japan, that the prevalence of positive rate of serum anti-H. pylori-IgG as well as H. pylori infection detected histological and by the 13 C-urea breath test is decreasing in longliving elderly, leading to a concomitant decrease of Helicobacter pylori virulence factors A Soltermann et al the prevalence of gastric cancer in subjects older than 85 years. 27 Concerning IM, the authors reported an increase with age in either H. pylori-negative or -positive patients.…”
Section: Discussionmentioning
confidence: 99%
“…In Japan and China, gastric adenocarcinoma is very common because, firstly, nearly all strains are of the most virulent pro-inflammatory cagApositive cytotoxic type and secondly because such strains usually cause a pan-or corpus-predominant gastritis in these populations with associated reduced acid secretion. 11 Thus in these populations, H. pylori would be expected more predictably to have a negative association with GORD and its complications, Barrett's oesophagus and oesophageal adenocarcinoma. This is indeed the case: studies from these countries consistently show a strong negative association.…”
Section: H Pylori and Gord Complications In East Asiamentioning
confidence: 98%
“…Feldman et al studied gastric acid secretion in elderly patients and found that basal acid output and peak acid output did not correlate with age (Feldman&Cryer, 1998). Similarly, Lijima et al, reported that gastric acid secretion was well preserved irrespective of ageing, however it seemed to increase with ageing in the H. pylori-negative subjects (Iijima et al, 2004). The decline in gastric acid secretion in H. pylori-positive patients depends on both an increasing prevalence of fundic atrophic gastritis and inflammatory cytokines, i.e., interleukin (IL) IL-1 and TNF-, which are known to inhibit parietal cells.…”
Section: Gastric Acid Secretionmentioning
confidence: 99%